2018
DOI: 10.3390/su10114239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impacts of Integrated Pollution on Water Quality of the Trans-Boundary Neris (Viliya) River

Abstract: The trans-boundary area between the Europe Union and other countries is highly susceptible to changes in water quality and variations in the potential pollution load that could influence its eco-systems significantly. The Neris (Viliya) River is one of the biggest surface water bodies in Lithuania and Belarus with an ecologically important area protected by international legislation. The study was aimed at evaluating the impacts of integrated pollution on water quality of the Neris River taking into account di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Wu discussed the key water quality indicators in Lake Taihu Basin, China, by using the minimum WQI method, which was developed based on a stepwise linear regression analysis, and the water quality was classified into five grades based on the WQI scores [41]. Many international water bodies have also been assessed for water quality by comprehensive multivariate statistical methods [44]. Considering the classification methods of various water quality grades, the actual situation of the Chinese water quality assessment standards, and the water quality management of this project, the classification of WQI values in this study were divided into five grades from 0 to 100, corresponding to the water quality levels from excellent to very poor, as seen in Table 2 and Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Wu discussed the key water quality indicators in Lake Taihu Basin, China, by using the minimum WQI method, which was developed based on a stepwise linear regression analysis, and the water quality was classified into five grades based on the WQI scores [41]. Many international water bodies have also been assessed for water quality by comprehensive multivariate statistical methods [44]. Considering the classification methods of various water quality grades, the actual situation of the Chinese water quality assessment standards, and the water quality management of this project, the classification of WQI values in this study were divided into five grades from 0 to 100, corresponding to the water quality levels from excellent to very poor, as seen in Table 2 and Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Appleton et al [1] highlighted the fluvial contamination of some artisanal and small scale gold mining (ASGM) areas in Southern Ecuador. Although this study was not as exhaustive as others that can serve as a methodological reference [2], it was the first objective evidence of the existence of relevant contents of As, Cd, Cu and Zn in surface waters in the Ponce Enríquez, Portovelo-Zaruma, and Nambija areas. Furthermore, their results prove that those heavy metal contents exceeded the WHO Drinking Water Guideline values, the USEPA Water Quality Criteria for the Protection of Aquatic Life and the Ecuadorian standards [3].…”
Section: Introductionmentioning
confidence: 96%
“…It has been reported that people's mental health can be improved in the absence of water pollution [5]. Therefore, it is urgent to evaluate the comprehensive water quality, understand the situation of water pollution, and identify the main pollution sources, to protect water resources and control water pollution [6,7].…”
Section: Introductionmentioning
confidence: 99%